HUBUNGAN ANTARA GRATITUDE DENGAN PERILAKU PROSOSIAL PADA ANGGOTA KOMUNITAS VESPA SALATIGA - Elang Patria Samudra,; Doddy Hendro Wibowo, (Jurnal Cakrawala Ilmiah, 2023)
In the current era, prosocial behavior is becoming increasingly rare and tends to become individualistic. This research aims to determine the relationship between gratitude with prosocial behavior among members of the Vespa Salatiga community. In this research, researchers used techniquesAccidental sampling for sampling members of the Vespa community in Salatiga, a total of 53 members of the Vespa Salatiga community who had been with the community for at least 3 years. The results of this study indicate a positive relationship between gratitude and prosocial behavior with a correlation coefficient value of r = 0.0274 and sig of 0.256 (p<0.05). This shows that there is a significant positive relationship between the variable gratitude and prosocial behavior among members of the Vespa Salatiga community.